A new skink of the genus Scincella Mittleman, 1950 (Squamata: Scincidae) from Hoa Binh Province, northern Vietnam - Pham, Anh Van; Pham, Cuong The; Le, Minh Duc; Ngoc, Hai Ngo; Ziegler, Thomas; Nguyen, Truong Quang (Zootaxa, 2024)
A new species of the genus Scincella Mittleman, 1950 is described from northern Vietnam based on morphological and molecular evidence. Scincella ouboteri sp. nov. is characterized by a combination of the following characters: Size medium (SVL up to 58.6 mm); primary temporals 2; external ear opening present, with 3 or 4 lobules on anterior margin; loreals 2; supralabials 7; infralabials 6 or 7; nuchals in 2–4 pairs; midbody scales in 30–32 rows; dorsal scales smooth, in 6 rows across the back; paravertebral scales 65–73, not widened; ventral scales in 65–71 rows; 10–12 smooth lamellae beneath finger IV and 18–20 beneath toe IV; toes overlapping fingers when limbs adpressed along body; dorsal surface of body and tail bronze-brown with a black vertebral stripe, in width of two dorsal scales, two bright dorsolateral stripes extending from behind the head to middle of tail, a dark stripe running from nostril to eye and extending from posterior margin of eye along upper part of flank and tail. In phylogenetic analyses, the new species and S. ochracea form an independent lineage sister to all other congeners included in the study.